2022
DOI: 10.3390/ani12121555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Moisture Levels and Additives on the Ensiling Characteristics and In Vitro Digestibility of Stylosanthes Silage

Abstract: The present study aims to estimate the dynamic effects of moisture levels and inoculants on the fermentation quality and in vitro degradability of Stylosanthes silage. In this experiment, Stylosanthes was ensiled with (1) no additive (control), (2) Lactobacillus plantarum (LP), (3) Lactobacillus plantarum carrying heterologous genes encoding multifunctional glycoside hydrolases (xg), or (4) LP + xg and was wilted until different moisture levels (60% and 72%) were attained. The ensiled bags were unpacked after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…This may reflect the fact that the added fibrocystic enzymes increased the hydrolysis of cell wall carbohydrates, decreased their fiber content, and increased the WSC content. This result is in agreement with the findings of Foster et al that the addition of cellulase to warm-season legumes and Bahia grass silage increased WSC content [35,38].…”
Section: Effect Of Moisture and Additives On The Chemical Composition...supporting
confidence: 93%
See 2 more Smart Citations
“…This may reflect the fact that the added fibrocystic enzymes increased the hydrolysis of cell wall carbohydrates, decreased their fiber content, and increased the WSC content. This result is in agreement with the findings of Foster et al that the addition of cellulase to warm-season legumes and Bahia grass silage increased WSC content [35,38].…”
Section: Effect Of Moisture and Additives On The Chemical Composition...supporting
confidence: 93%
“…At W3, in vitro digestibility was significantly increased in mixed silage under E and M treatments compared with U and L treatments. So we can infer that in vitro digestibility and NDF and ADF contents were negatively correlated, and our conclusions were the same as those of Bao et al [35].…”
Section: Effect Of Moisture and Additives On The Chemical Composition...supporting
confidence: 88%
See 1 more Smart Citation
“…The decrease in detergent fiber degradation is related to the reduced starch availability when the amount of corn is reduced, and mango silage is increased. The values of detergent fiber degradation in the treatments ( Table-4 ) can be attributed to the fact that the hay used in making the waste mango silage received a chemical treatment with lactic acid to improve the availability of structural carbohydrates attached to lignin [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in digestibility is owing to the higher fibrous fractions present in the thatch of this legume, which contribute to the reduction in digestibility. Bao et al (2022) evaluated the effect of different moisture contents and additives on silage characteristics and in vitro digestibility of Stylosanthes silage and found that IVDMD was negatively correlated with NDF and ADF contents, and that the higher the fiber content, the lower the digestibility, negatively affecting the consumption of DM by animals. TDN content also reduced with increasing levels of legume in the silage (Figure 5c), with the minimum point (597 g kg -1 DM) reached at the level of 35.38% Pigeon pea addition.…”
Section: Quality Of Silagesmentioning
confidence: 99%